2007
DOI: 10.1186/1471-2296-8-32
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of missed test results and associated treatment delays in a highly computerized health system

Abstract: Background: Diagnostic errors associated with the failure to follow up on abnormal diagnostic studies ("missed results") are a potential cause of treatment delay and a threat to patient safety. Few data exist concerning the frequency of missed results and associated treatment delays within the Veterans Health Administration (VA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 29 publications
2
62
0
2
Order By: Relevance
“…6 In the Gopalan study, the researchers incorrectly assumed that, due to ADA guidelines, HbA1C would be tested at least once within a 6 month period. 7,8,9 One study has shown a high missing data rate but high accuracy for HbA1C data; 10 and a diabetes RCT has recognized and planned accordingly for missing HbA1C data. 11…”
Section: Study Design Recommendationsmentioning
confidence: 99%
“…6 In the Gopalan study, the researchers incorrectly assumed that, due to ADA guidelines, HbA1C would be tested at least once within a 6 month period. 7,8,9 One study has shown a high missing data rate but high accuracy for HbA1C data; 10 and a diabetes RCT has recognized and planned accordingly for missing HbA1C data. 11…”
Section: Study Design Recommendationsmentioning
confidence: 99%
“…4 Comprehensive electronic result management systems have been successfully implemented in ambulatory settings; 16,17 however, gaps in test result management remain. 18 Initial attempts to improve inpatient test result management have not shown significant impact. 12,19 These results have illustrated that the workflow of hospital-based clinicians and the requirement to ensure follow-up of results after discharge from the hospital may necessitate different result management solutions for inpatient providers than those implemented in the ambulatory setting.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have introduced the "pre-pre-" and "post-post-" analytical phases to identify activities associated with the initial selection of tests and with the interpretation by clinicians respectively, to differentiate them for the pure collection/transport activities (pre-analytical phase) and reporting (postanalytical phase) 13, 14 . There is some evidence that these steps are more error-prone than other pre-and postanalytical activities [13][14][15][16][17][18] .However, the definition and use of such terms is not universal. Indeed the definition of even basic terms such as pre-analytical, analytical and post-analytical can vary between authorities.…”
Section: Introductionmentioning
confidence: 99%